Hepatoprotective role of PXR activation and MRP3 in cholic acid-induced cholestasis - Teng, S (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: Activation of the pregnane X receptor (PXR) has been shown to protect against cholestatic hepatotoxicity. As PXR alters the expression of numerous hepatic bile acid transporters, we sought to delineate their potential role in hepatoprotection. EXPERIMENTAL APPROACH: Wild-type (PXR(+/+)) and PXR-null (PXR(-/-)) mice were fed a 1% cholic acid (CA) diet with or without the PXR activator, PCN. Liver function was assessed along with the corresponding changes in hepatic gene expression. KEY RESULTS: CA administration caused significant hepatotoxicity in PXR(+/+) mice and was associated with induction of several FXR and PXR regulated genes, which encode for bile acid transport and metabolizing proteins. Compared to CA alone, co-administration of PCN to CA-fed PXR(+/+) mice significantly decreased hepatotoxicity and was associated with induction of MRP3 mRNA as well as CYP3A11 mRNA and functional activity. Unexpectedly, PXR(-/-) mice, which expressed significantly higher basal and CA-induced levels of MRP2, MRP3, OSTα, OSTβ, OATP2 and CYP3A11, were dramatically less sensitive to CA hepatotoxicity than PXR(+/+) mice. CONCLUSIONS: Protection of PXR(+/+) mice against CA-induced hepatotoxicity by PCN is associated with the induction of MRP3 and CYP3A11 expression. Resistance against CA-induced hepatotoxicity in PXR(-/-) mice may result from higher basal and induced expression of bile acid transporters, particularly MRP3. These findings emphasize the importance of transport by MRP3 and metabolism as major protective pathways against cholestatic liver injury.